Uji Antagonisme Jamur Endofit Terhadap Cercospora oryzae Miyake dan Culvularia lunata (Wakk) Boed. dari Tanaman Padi di Laboratorium - Ida Rumia Manurung; Mukhtar Iskandar Pinem; Lahmuddin Lubis (Universitas Sumatera Utara, 2014)
The objective of the research was to test antagonism ability of endophytic fungi to control C. oryzaeand C. lunata in laboratory. This research was conducted in Plant Disease Laboratory,Agroecotechnology Program Study, Faculty of Agriculture, University of Sumatera Utara, Medan(± 25 m asl) from November 2013 until February 2014. The method used was RandomizedComplete Design with two factors in 3 replications. The first factor was the pathogens (C. oryzaeand C. lunata) and the second factor was the endophytic fungi (Penicillium sp., Trichoderma spp.,Aspergillus sp1., Trichocladium sp., Aspergillus sp2. and Nigrospora sp.). Parameters observedwere inhibiting zone, width of inhibiting zone, diameter of pathogen colony and growth width ofpathogen colony. The results of this research showed that the pathogens, the endophytic fungi andinteraction between them affected significantly to the inhibiting zone, width of inhibiting zone,diameter of pathogen colony and growth width of pathogen colony . The good result to controlC. oryzae was showed on P1E2 (C. oryzae + Trichoderma spp.) with 67,56% andP1E5 (C. oryzae + Aspergillus sp2.) with 67,52% and to control C. lunata on P2E1(C. lunata + Penicillium sp.) with 70,10% in inhibiting zone.Key words: C. oryzae, C. lunata, endophytic fungi, rice